2021
DOI: 10.3390/ijerph18116149
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Emergency Department Nurses’ Compliance with Standard Precautions Using Multilevel Analysis

Abstract: Standard precautions protect patients and nurses from infection. Nevertheless, compliance with standard precautions is lower among emergency department nurses than other nurses. We examined the individual and organizational factors that influence emergency department nurses’ compliance with standard precautions via a cross-sectional study. A self-reported questionnaire survey was administered to 140 nurses working in nine emergency departments in South Korea. It included items regarding ethical awareness and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The results of this study showed that the overall total compliance rate of the studied nurses was optimal (more than 90%). The mean scores of standard precautions ranged from 3.1 to 3.9 out of 4, this finding is similar to the findings of previous studies who reported that the mean compliance with standard precautions among emergency nurses was 4.29 and 4.31 out of 5, respectively that used the same instrument ( 20 , 21 ). In another study conducted among Saudi nursing students using a similar CSPS tool ( 17 ), results show the overall compliance rate of the students with standard precautions was moderate (60.1%).…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study showed that the overall total compliance rate of the studied nurses was optimal (more than 90%). The mean scores of standard precautions ranged from 3.1 to 3.9 out of 4, this finding is similar to the findings of previous studies who reported that the mean compliance with standard precautions among emergency nurses was 4.29 and 4.31 out of 5, respectively that used the same instrument ( 20 , 21 ). In another study conducted among Saudi nursing students using a similar CSPS tool ( 17 ), results show the overall compliance rate of the students with standard precautions was moderate (60.1%).…”
Section: Discussionsupporting
confidence: 90%
“…16 Kim and Lee also confirmed that individual factor has a significant relationship with compliance with standard infection prevention precaution (46.7%). 17 In an Ethiopian study compliance was low among healthcare workers due to insufficient knowledge poses devastating consequences in PHC, interventions such as staff on standard infection prevention precautions and consistent managerial support are required. 13,18 Difficulty to use the PPE was found to be an individual factor affecting compliance with standard infection prevention precautions on the use of PPE.…”
Section: Decision Rulementioning
confidence: 99%